1966
DOI: 10.1063/1.1707961
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transitions of Ethylene Oxide Polymers

Abstract: Glass transition temperatures of a very wide molecular-weight range of ethylene oxide polymers were measured by mechanical loss and by broadline NMR. Starting at about -95°C for ethylene glycol, the glass transition rises to a maximum of -17° for molecular weight 6000 and then drops off to -53° for polymers with molecular weights greater than 200 000. This unusual behavior is probably caused by the high crystallinity of the intermediate molecular-weight polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

1970
1970
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(76 citation statements)
references
References 15 publications
5
70
1
Order By: Relevance
“…By using broadline proton nuclear magnetic resonance, Faucher et al showed that T g of PEG increased from -49°C for PEG 400 to a maximum of -20°C for PEG 6000 and then decreased with molecular weight. 20 However, in the current study, dispersions containing IMC and PEG 6000 displayed T g s well below -20°C ( Figure 4), suggesting that the T g of pure PEG 6000 must be much lower than -20°C.…”
Section: Composition-dependent Glass Transition Temperature (T G ) Shmentioning
confidence: 77%
“…By using broadline proton nuclear magnetic resonance, Faucher et al showed that T g of PEG increased from -49°C for PEG 400 to a maximum of -20°C for PEG 6000 and then decreased with molecular weight. 20 However, in the current study, dispersions containing IMC and PEG 6000 displayed T g s well below -20°C ( Figure 4), suggesting that the T g of pure PEG 6000 must be much lower than -20°C.…”
Section: Composition-dependent Glass Transition Temperature (T G ) Shmentioning
confidence: 77%
“…[89] For example, ethylene glycol (n ¼ 1) exhibits a T g ¼ À93 8C, a value which increases to À50 8C when 9 ethylene oxide units are placed in the chain. The T g of monomer 9, possessing 4 ethylene oxide units, falls in an intermediate range (À75 8C), which was deemed Chain-End and Chain-Internal Crosslinking in ''Latent Reactive'' Silicon Elastomers sufficiently low for our study.…”
Section: Resultsmentioning
confidence: 99%
“…With convenient geometrical alignment of its polymer chains, PEO is a semicrystalline material with a reported crystallinity as high as 72% and a melting point in the range of 60-75 C. 27 The Tg of the amorphous regions of PEO has been reported to be À53 C. 28 With a rigid structure and a bulky carboxyl side group, PAA can only exist in an amorphous form. DSC profiles of the physical blend and IPC of Polyox N12K and Carbopol 907 are presented in Figure 5.…”
Section: Properties Of the Ipc Between Polyox N12k And Carbopol 907mentioning
confidence: 99%